(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an overview of the classification of English consonants, which is essential for understanding their roles in pronunciation and phonetics. Consonants are categorized by three primary criteria: “place of articulation” (the location within the vocal tract where the sound is produced), “manner of articulation” (how airflow is modified as it passes through the vocal tract), and “voicing” (whether the vocal cords vibrate during sound production). The article further breaks down each criterion, discussing how each one applies to English consonants. Understanding these classifications is beneficial for linguists, language educators, and speech therapists. For example, knowing the distinctions between voiced and voiceless sounds or understanding how various articulatory placements influence pronunciation can help educators teach clearer and more accurate pronunciation. A summary table organizes consonants by their classifications, offering a quick reference for each sound’s specific features. This structured approach makes it easier to see patterns in English phonology and helps learners grasp the nuances of English consonant sounds more effectively.